Spatial and environmental influences on selection in a clock gene coding trinucleotide repeat in Canada lynx (Lynx canadensis) - Melanie B. Prentice; Jeff Bowman; Dennis L. Murray; Kamal Khidas; Paul J. Wilson (Molecular Ecology, 2020)
Clock genes exhibit substantial control over gene expression and ultimately life‐histories using external cues such as photoperiod, and are thus likely to be critical for adaptation to shifting seasonal conditions and novel environments as species redistribute their ranges under climate change. Coding trinucleotide repeats (cTNRs) are found within several clock genes, and may be interesting targets of selection due to their containment within exonic regions and elevated mutation rates. Here, we conduct inter‐specific characterization of the NR1D1 cTNR between Canada lynx and bobcat, and intra‐specific spatial and environmental association analyses of neutral microsatellites and our functional cTNR marker, to investigate the role of selection on this locus in Canada lynx. We report signatures of divergent selection between lynx and bobcat, with the potential for hybrid‐mediated gene flow in the area of range overlap. We also provide evidence that this locus is under selection across Canada lynx in eastern Canada, with both spatial and environmental variables significantly contributing to the explained variation, after controlling for neutral population structure. These results suggest that cTNRs may play an important role in the generation of functional diversity within some mammal species, and allow for contemporary rates of adaptation in wild populations in response to environmental change. We encourage continued investment into the study of cTNR markers to better understand their broader relevance to the evolution and adaptation of mammals.